2001
DOI: 10.1023/a:1010385832566
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although information processing has been widely studied with depressed adults, little emphasis has been placed on the specificity of resultant findings to depression, as opposed to other psychological disorders. Analogously, even less effort has been directed toward examining the information processing styles of depressed children and adolescents. The present study investigated the specificity of information processing styles to depression and anxiety among 58 youth psychiatric inpatients. To assess informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…The relationship between positive processing and depression was consistent with previous studies (2012; Gençöz et al, 2001; Hammen & Zupan, 1984; Hayden, Olino, Mackrell, et al, 2013; Prieto et al, 1992; Timbremont & Braet, 2004; Zupan, Hammen, & Jaenicke, 1987). However, the literature on negative processing and depression in youth is less consistent, with some studies (Prieto et al, 1992; Timbremont & Braet, 2004; Zupan, Hammen, & Jaenicke, 1987), but not others (e.g., Alloy et al, 2012; Black & Pössel, 2013; Gençöz et al, 2001; Hammen & Zupan, 1984) reporting a significant association. In some cases, non-significant findings may be due to sample sizes too small to detect small-to-medium effects and to methodological differences, such as the lack of a sad mood induction prior to the SRET, which is important for detecting associations between SRET performance and depressive vulnerabilities (Evraire et al, in press).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The relationship between positive processing and depression was consistent with previous studies (2012; Gençöz et al, 2001; Hammen & Zupan, 1984; Hayden, Olino, Mackrell, et al, 2013; Prieto et al, 1992; Timbremont & Braet, 2004; Zupan, Hammen, & Jaenicke, 1987). However, the literature on negative processing and depression in youth is less consistent, with some studies (Prieto et al, 1992; Timbremont & Braet, 2004; Zupan, Hammen, & Jaenicke, 1987), but not others (e.g., Alloy et al, 2012; Black & Pössel, 2013; Gençöz et al, 2001; Hammen & Zupan, 1984) reporting a significant association. In some cases, non-significant findings may be due to sample sizes too small to detect small-to-medium effects and to methodological differences, such as the lack of a sad mood induction prior to the SRET, which is important for detecting associations between SRET performance and depressive vulnerabilities (Evraire et al, in press).…”
Section: Discussionsupporting
confidence: 92%
“…While some studies found that depressive symptoms were associated with both diminished recall of positive, and enhanced recall of negative self-referent adjectives (e.g. Prieto et al, 1992; Timbremont & Braet, 2004; Zupan, Hammen, & Jaenicke, 1987), others report that the effects are limited to reduced positive recall (e.g., Gençöz et al, 2001; Hammen & Zupan, 1984). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Depressive symptoms also were correlated with increased proportional recall of endorsed negative self-referent adjectives, and decreased recall of endorsed positive self-referent adjectives. These results complement hypotheses that individuals with negative self-schemas would encode negative self-referent information more deeply and in turn recall this information to a greater extent than positive self-referent information; findings are similar to those reported in studies assessing SRET performance in dysphoric or clinically depressed samples of adults (Dozois & Dobson, 2001; Fritzsche et al, 2010; Gotlib et al, 2004) and youth (Gençöz et al, 2001; Hammen & Zupan, 1984). Of note, this is the first study to report concurrent associations between depressive symptoms and RT and recall biases on the SRET in a nonclinical adolescent sample, suggesting that these information processing biases may be associated with the emergence of depressive symptoms during this age range.…”
Section: Discussionsupporting
confidence: 84%
“…Studies of depressed adults and youth have reported findings of increased negative adjective endorsement and recall and decreased positive adjective endorsement and recall (Dozois & Dobson, 2001; Gençöz, Voelz, Gençöz, Pettit, & Joiner, 2001; Hammen & Zupan, 1984, Fritzsche et al, 2010). A subset of SRET studies also have explored the efficiency with which individuals process schema-congruent information by measuring the speed with which individuals make endorsements on the SRET, positing that judgments congruent with one's schema should be made more quickly and efficiently than those that are less central to one's self-concept (Kuiper & MacDonald, 1982).…”
mentioning
confidence: 99%